ATYPICAL MYCOBACTERIAL INFECTION - Aleksander Popov; Klimentina Gospodinova; Milen Karaivanov (Peytchinski Publishing, 2024)
We describe a 47-year-old healthy man who, after an injury to the third finger of the right hand, developed a reddened papule that did not disappear. Over a period of three months, edema developed on the finger and dorsum of the right hand, followed by several variegated nodules along the 3rd finger, dorsum of the right hand, and right forearm. There are no subjective complaints. The patient has an aquarium at home, and the complaints coincide with a period of growth of the fish in it. The diagnosis of Mycobacterium marinum infection is made on the basis of history, clinical picture, histology and molecular genetic testing for mycobacteria. Treatment with numerous antibacterial agents was carried out, and the long-term (9 months) therapy with clarithromycin, rifampicin and ethambutol, appointed after the diagnostic clarification, led to the cure of the infection. A brief review of the literature on the issue is made.